Gliosarcoma arising from oligodendroglioma (Oligosarcoma): A case report with genetic analyses. Issue 10 (23rd September 2018) - Tanaka, Shunya; Hitotsumatsu, Tsutomu; Sugita, Yasuo; Ishido, Katsuya; Ito, Osamu; Hatae, Ryusuke; Akagi, Yojiro; Yoshimoto, Koji; Iihara, Koji
Abstract : Gliosarcomas are a type of bimorphic tumor composed of glial and sarcomatous elements, and are considered to be a variant of glioblastoma, WHO grade IV. To date, only rare cases of gliosarcoma with oligodendroglial components (oligosarcoma) have been reported. We report a case of oligosarcoma consisting of gliosarcoma arising from recurrent oligodendroglioma. A 53‐year‐old man, who had undergone a gross total resection of oligodendroglioma (WHO grade II) 11 years earlier, presented with a local tumor recurrence. The patient underwent a second gross total resection, whereupon a histopathological examination further revealed residual features of classical oligodendroglioma, and newly‐developed sarcomatous characteristics. Both the primary and recurrent tumors showed 1p/19q co‐deletion and mutation of the isocitrate dehydrogenase 1 (IDH1) gene, consistent with being oligodendroglial in nature. Loss of heterozygosity (LOH) of chromosome 1p/19q and IDH1 mutation have seldom been analyzed in previous reports of oligosarcomas. We report a rare case study supported by the results of genetic analyses. Our analyses have revealed that the sarcomatous component represents a metaplastic change occurring in the oligodendroglial element.